POST-CONFLICT; PARTICIPATION WOMEN AND EMPOWERMENT IN NORTH ACEH - Hasni, Khairul; Wahyuni, Sri; Azhar, Al-; Yusrawati, Yusrawati (Marwah: Jurnal Perempuan, Agama dan Jender, 2025)
Acehnese women living in rural areas during the conflict immediately experienced economic problems and violations. Entering a normal phase, rural women returned to their roles outside the home, helping to build the family economy. Inequality in various sectors has exacerbated the powerlessness of women living in these areas, particularly in economic matters. This study analyzes the forms of post-conflict women's participation and the obstacles they face in economic empowerment. The documents in this study are supported by various field data, informal interviews, and various sources of information from research literature on the burdens of rural women qualitatively. The results of the study indicate that women in North Aceh, particularly in the rural communities of Nisam, Guha Ulue, Alue Rambe, and Pulau Iboh in Kutamakmur District, are mostly farmers who also work as housewives. Their participation is still lacking in the planning, implementation, and evaluation of village development. Women's empowerment in Aceh faces various structural problems, including patriarchy, discriminatory interpretations of Islamic Sharia law, poverty, and low levels of political participation at the village level. The research findings indicate that rural women in Aceh have significant potential and a strategic role in village development but still face various cultural and structural barriers that limit their participation in empowerment.